Comparison of the Ocular Microbiomes of Dry Eye Patients With and Without Autoimmune Disease - Qi, Yun; Wan, Yong; Li, Tianhui; Zhang, Ming; Song, Yu; Hu, Yaguang; Sun, Yining; Li, Li (Frontiers in Cellular and Infection Microbiology, 2021)
Purpose The pathogenesis of dry eye concomitant with autoimmune disease is different from that of dry eye without autoimmune disease. The aim of this study was to explore differences in the microbiota diversity and composition in dry eye with and without autoimmune disease. Methods Swab samples from the inferior fornix of the conjunctival sac were obtained from dry eye patients without autoimmune disease (n = 49, dry eye group) and from those with autoimmune disease (n = 38, immdry eye group). Isolated bacterial DNAs from swabs were analyzed with 16S rRNA amplicon sequencing. Results Analysis of the alpha diversity revealed no significant differences between subjects in the dry eye and immdry eye groups. Those in the immdry eye group had a distinct microbial composition compared with those in the dry eye group. The combination of the genera Corynebacterium and Pelomonas distinguished subjects in the immdry eye group from those in the dry eye group, with an area under the curve of 0.73 (95% CI = 0.62–0.84). For the same bacteria, the correlations between microbe abundance and the ocular surface parameters were different in the two groups. In addition, the functions of the microbial communities were altered in the two groups. Conclusions Our study demonstrates changes in the composition and function of the ocular microbiome between subjects in the immdry eye and dry eye groups, which suggests that the potential pathogenesis is different.